Response of vagal afferent neurons to macronutrients - Öztürk, Rabia İclal; Şekeroğlu, Ramazan; Öztürk, Gürkan (Karger, 2018)
[Abstract Not Available]
3rd International Congress of the Turkish-Neuroendocrinology-Society -- JUN 29-JUL 01, 2018 -- Malatya, TURKEY
WOS: 000445952400033
Keywords: Response; Vagal Afferent Neurons; Macronutrients